Dishevelled2 activates WGEF via its interaction with a unique internal peptide motif of the GEF - Omble, Aishwarya; Mahajan, Shrutika; Bhoite, Ashwini; Kulkarni, Kiran (COMMUNICATIONS BIOLOGY, 2024)
The Wnt-planar cell polarity (Wnt-PCP) pathway is crucial in establishing cell polarity during development and tissue homoeostasis. This pathway is found to be dysregulated in many pathological conditions, including cancer and autoimmune disorders. The central event in Wnt-PCP pathway is the activation of Weak-similarity guanine nucleotide exchange factor (WGEF) by the adapter protein Dishevelled (Dvl). The PDZ domain of Dishevelled2 (Dvl2PDZ) binds and activates WGEF by releasing it from its autoinhibitory state. However, the actual Dvl2PDZ binding site of WGEF and the consequent activation mechanism of the GEF have remained elusive. Using biochemical and molecular dynamics studies, we show that a unique ``internal-PDZ binding motif'' (IPM) of WGEF mediates the WGEF-Dvl2PDZ interaction to activate the GEF. The residues at P 2 , P 0 , P -2 and P -3 positions of IPM play an important role in stabilizing the WGEFpep-Dvl2PDZ interaction. Furthermore, MD simulations of modelled Dvl2PDZ-WGEFIPM peptide complexes suggest that WGEF-Dvl2PDZ interaction may differ from the reported Dvl2PDZ-IPM interactions. Additionally, the apo structure of human Dvl2PDZ shows conformational dynamics different from its IPM peptide bound state, suggesting an induced fit mechanism for the Dvl2PDZ-peptide interaction. The current study provides a model for Dvl2 induced activation of WGEF. This study identifies a unique ``internal-PDZ binding motif'' (IPM) of WGEF that mediates its interaction with Dvl2PDZ, leading to the release of GEF from its autoinhibitory state. It further unravels the underlying mutual Dvl2-IPM recognition aspects.